Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 1999)
Welcome to the second issue of Networks. A new journal takes a while to become established, but we are gratified by the interest that the first issue aroused and pleased to be able to publish the second in this school year.